Pengaruh Kompetensi, Motivasi dan Pelatihan Aplikasi Sistem Penatausahaan SIMAK-BMN Terhadap Kualitas Kinerja Personil Disbekal TNI AL - Arifin, Ahmad; Sirait, Binsar Mangaratua; Setiawan, Daniel (Rekayasa, 2021)
The research was carried out with the aim of knowing how influential the implementation of training from the application of the State Property Accounting Management Information System (SIMAK BMN) administration system and the motivation and competence of Disbekal personnel to the improvement of the quality of Disbekal personnel's performance. The data collection technique was by distributing questionnaires, where the research population was personnel in the accounting department of BMN at the Disbekal Head Office and DKI Jakarta Regional Office, the entire population of 320 Disbekal personnel in this study was used as a sample. Data analysis using statistical methods with independent variables are competence, motivation, and SIMAK-BMN training, while the dependent variable is the quality of personnel performance. It was found that SIMAK-BMN training had a significant effect on the quality of the performance of the Disbekal personnel, motivation and competence affected the performance of the Disbekal personnel.